Pengaruh Politik Uang dalam Pemilu Berdasarkan Perspektif Mahasiswa PPKn Unimed Stambuk 2021 - Manik, Vinolya Lidevia Br; Siregar, Rahmi; Situmorang, Amelia; Manurung, Mario Fany; Ivanna, Julia (Lembaga Intelektual Muda (LIM) Maluku, 2023)
Elections are a means for the people to provide legitimacy for the ruler who will lead for 5 (five) years. One of the problems that always arises in the implementation of elections is money politics. Money is one of the factors that influence elections. This study aims to explore the influence of money politics in elections based on the perspective of Pancasila and Civic Education (PPKn) students at Medan State University (Unimed) Stambuk 2021. The type of research used is survey method by looking for several respondents from the PPKn Department. The research instrument used is a questionnaire to determine the perception of respondents. Data analysis is carried out descriptively based on data obtained through respondents. The results showed that money politics influences elections with a high degree of influence. The influence of money politics on elections also differs based on the type of candidate. Money politics affects more for new candidates than for old candidates. The political influence of money also differs based on the type of party. Money politics has a greater influence on new parties than for old parties The results of this study show that money politics is an important factor in influencing elections